Penerapan Argumentasi dan Bahan Ajar dalam Meningkatkan Pemahaman Materi Biologi Mahasiswa - Kencanawati, Indah (Pedagogi Hayati, 2023)
Teaching materials have a very crucial role in strengthening arguments during the biology learning process. With good teaching materials, information can be presented systematically and structured, making it easier for students to understand biological concepts and deepen their understanding of scientific principles. Scientific argumentation aimed at reaching a rational perpestive on science, scientific concepts, or elements within a scientific procedure.This study is experimental research employing a pretest-post-test control group design. The research was conducted with a population of 44 fifth-semester students majoring in biology education. The sample selection was performed using random sampling, consisting of two classes (experimental and control), the experimental class consisted of 22 students, and the control class consisted of 22 students. Research data on the application of argumentation and teaching materials in improving students' understanding of biology material was obtained through pretest and posttest.for the research were collected through pretests and post-test, which included 10 questions with five argumentation indicators via the minimum structure essay test. The research findings demonstrated an enhancement in students' ability to articulate their comprehension of the material when utilizing teaching materials compared to those who did not. As a result, it is recommended that the availability of teaching materials be applied in the learning process in other courses to help improve skills in understanding biological material in arguing including the presentation of claims, data, warrants, backing, and effective rebuttals in the learning process.